2019
DOI: 10.1002/jmor.21072
|View full text |Cite
|
Sign up to set email alerts
|

Unique features of the skin barrier in naked mole rats reflect adaptations to their fossorial habitat

Abstract: The stratum corneum (SC), the top layer of the epidermis, is the functional site of the skin barrier and serves to maintain hydration of the body by preventing water loss and thwarting the entrance of pathogens. The naked mole rat (NMR) (Heterocephalus glaber) is a rodent that resides in hypoxic underground tunnels in arid Africa. NMRs are not only hairless; their skin is devoid of glands and pain sensation. To understand how the skin barrier of the NMR is uniquely adapted to this environment, skin samples fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…In general, these characteristics were already expected since the ear skin for mammals in general presents the same patterns of ultrastructural organization (Khavkin & Ellis 2011, Biggs et al 2020. Among the species that present the same ultrastructural patterns of the skin, there are pacas (Cuniculus paca) (Isola et al 2013), naked mole rat (Heterocephalus glaber) (Menon et al 2019) and mouse (Allen & Potten 1976) stand out (Morita et al 1995). Still, this same pattern was also observed in the skin of Cuban crocodile (Crocodylus rhombifer) (Szewczyk & Stachewicz 2020) and in the skin of humans (Roger et al 2019).…”
Section: Discussionmentioning
confidence: 74%
“…In general, these characteristics were already expected since the ear skin for mammals in general presents the same patterns of ultrastructural organization (Khavkin & Ellis 2011, Biggs et al 2020. Among the species that present the same ultrastructural patterns of the skin, there are pacas (Cuniculus paca) (Isola et al 2013), naked mole rat (Heterocephalus glaber) (Menon et al 2019) and mouse (Allen & Potten 1976) stand out (Morita et al 1995). Still, this same pattern was also observed in the skin of Cuban crocodile (Crocodylus rhombifer) (Szewczyk & Stachewicz 2020) and in the skin of humans (Roger et al 2019).…”
Section: Discussionmentioning
confidence: 74%
“…Research on humans, laboratory and domestic mammals show that skin pH varies with season (human skin most acidic in July), body part, sex, age, species and breed ( Byrd et al , 2018 ; Chikakane and Takahashi, 1995 ; Matousek and Campbell, 2002 ; Meyer and Neurand, 1991 ). Skin pH of wildlife has rarely been studied ( Supplementary Table S1 ), but does include data for various bird species and naked mole rats ( Heterocephalus glaber ) in zoos ( Bartels et al , 1991 ; Menon et al , 2019 ) and amphibians and fish in laboratories ( Tsui et al , 2002 ; Litwiller et al , 2006 ; Woodhams et al , 2012 ; Barnhart et al , 2020 ). Skin pH has not yet been quantified in free-ranging populations but may be an important component in assessing both inter- and intra-specific responses to infectious pathogens.…”
Section: Introductionmentioning
confidence: 99%
“…We also found in this study that middle-aged NMR showed a histological skin structure similar to the young ones, to the exception that the epidermal thickness was paradoxically increased at higher age as a consequence of increased number of epidermal layers. Marked thickness of the corneous layer in the adult NMR has previously been shown (10) and lack of fur has also been described to be compensated by a thicker epidermis (9)…”
Section: Discussionmentioning
confidence: 98%
“…To date, many of the NMR anti-aging mechanisms are poorly understood. Further, only two descriptive scientific articles have focused their research on NMR’s skin investigating how the skin morphology of these animals is adapted to thermoregulation and their subterranean environment( 9 , 10 ). However, skin remains an ideal organ for the analysis of several types of biological phenomena that can be associated with aging.…”
Section: Introductionmentioning
confidence: 99%